EFFECT OF A NEW ULTRASHORT BETALYTIC AGENT ON ACONITINE-INDUCED ARRHYTHMIA - Bartosova, Ladislava; Novak, Filip; Frydrych, Marek; Parak, Tomas; Opatrilova, Radka; Brunclik, Vit; Kolevska, Jana; El Moataz, Elnaggar; Necas, Jiri (Biomedical papers, 2005)
The anti-arrhythmic effect was tested on the model of aconitine-induced arrhythmia. The experiment was performed in vivo with 31 male Wistar laboratory rats. Group A was first administered aconitine and, after the onset of the first sinus rhythm disorders, the 44Bu compound was administered. Group B was first administered the 44Bu compound and only after that the aconitine. The control group was administered aconitine and saline as a replacement of the tested compound. In group A, there was a decrease in the ventricular fibrillation occurrence from 100 % to 8 % (p < 0.001) after the administration of the 44Bu compound. In the B group, the onsets of all monitored arrhythmia types were delayed by an average of 15.6 min. Ventricular rhythm occurrence was decreased from 100 to 20 %, as well as ventricular fibrillations, from 100 to 0 % (p < 0.001).
Keywords: Experimental pharmacology/Rats/Ester-functional group/Aconitine/Ventricular fibrillations